Recent Progress in Applications of Non-Thermal Plasma for Water Purification, Bio-Sterilization, and Decontamination - Azadeh Barjasteh; Zohreh Dehghani; Pradeep Lamichhane; Neha Kaushik; Eun Ha Choi; Nagendra Kumar Kaushik (Applied Sciences, 2021)
Various reactive oxygen and nitrogen species are accompanied by electrons, ultra-violet (UV) radiation, ions, photons, and electric fields in non-thermal atmospheric pressure plasma. Plasma technology is already used in diverse fields, such as biomedicine, dentistry, agriculture, ozone generation, chemical synthesis, surface treatment, and coating. Non-thermal atmospheric pressure plasma is also considered a promising technology in environmental pollution control. The degradation of organic and inorganic pollutants will be massively advanced by plasma-generated reactive species. Various investigations on the use of non-thermal atmospheric pressure plasma technology for organic wastewater purification have already been performed, and advancements are continuing to be made in this area. This work provides a critical review of the ongoing improvements related to the use of non-thermal plasma in wastewater control and outlines the operational principle, standards, parameters, and boundaries with a special focus on the degradation of organic compounds in wastewater treatment.